Low-voltage reactor double-layer insulation protective core resistant to high-salt mist corrosion and preparation method

CN122628629BActive Publication Date: 2026-10-09ENGER ELECTRIC (ZHUHAI) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611083969.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-09
Estimated Expiration
2046-07-21

AI Technical Summary

Technical Problem

[0005]为了克服现有技术防护性能弱、耐腐蚀使用寿命短的缺陷,提供分层绝缘防护铁芯结构,提升电抗器铁芯的防锈能力、电气绝缘性能、抗盐雾腐蚀性能,本申请提供一种耐高盐雾腐蚀的低压电抗器双层绝缘防护铁芯及制备方法

Benefits of technology

1.采用内层防锈绝缘涂层+外层耐蚀绝缘涂层的双层功能防护结构,分别实现铁芯缝隙内部防锈钝化、外部腐蚀介质阻隔防护功能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a low-voltage reactor double-layer insulation protective core resistant to high-salt-mist corrosion and a preparation method, and relates to the field of electrical insulation protective materials.The core comprises a silicon steel sheet laminated core, an inner anti-rust insulation coating, a coil wound on the outer side of the core and an outer corrosion-resistant insulation coating.The inner anti-rust insulation coating comprises the following raw materials: silicone-modified bisphenol F epoxy resin, methylphenyl silicone resin, nano zinc phosphate, mica powder, nano silicon dioxide, polyamide curing agent, silane coupling agent KH-560, defoaming agent, leveling agent and mixed solvent.The outer corrosion-resistant insulation coating comprises the following raw materials: phenolic epoxy resin, fluorine-modified acrylic resin, strontium chromate, glass flake, nano zinc oxide, alicyclic amine curing agent, salt-mist-resistant auxiliary agent, ultraviolet absorber and composite solvent.The application provides a layered insulation protective core structure, which improves the anti-rust capability, electrical insulation performance and salt-mist corrosion resistance of the reactor core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrical insulation and protective materials, and in particular to a double-layer insulating protective core for low-voltage reactors resistant to high salt spray corrosion and its preparation method. Background Technology

[0002] Reactors function as resistors to prevent changes in current within a circuit. They can be classified into air-core reactors and iron-core reactors. Iron-core reactors are constructed by winding conductors into a solenoid and then inserting an iron core inside the solenoid, thus achieving greater inductance.

[0003] Low-voltage reactors are widely used in power distribution systems in ports, offshore wind power, chemical industrial parks, and saline-alkali areas. These areas are often exposed to high concentrations of salt spray and acidic corrosive gases, causing reactor equipment to operate under strong corrosive conditions for extended periods. This places higher demands on the insulation and corrosion resistance of the reactor core.

[0004] The core protection of existing reactors generally adopts a single insulating varnish coating method. The resin system of the insulating varnish is mostly ordinary epoxy resin, alkyd resin, or pure organosilicon resin, and the filler is mostly monomeric anti-rust powder. This technical solution with consistent internal and external protection has the following shortcomings: it cannot simultaneously protect the internal rust of the core laminations from external atmospheric corrosion, the lamination gaps are prone to rust spots, increasing the magnetic loss of the equipment; it has weak resistance to chloride ion and corrosive gas penetration, resulting in a short service life due to salt spray corrosion; and the coating adhesion is low, making it prone to cracking and peeling under alternating temperature conditions. Summary of the Invention

[0005] In order to overcome the shortcomings of existing technologies such as weak protective performance and short service life due to corrosion, and to provide a layered insulating protective core structure to improve the rust prevention, electrical insulation performance and salt spray corrosion resistance of reactor cores, this application provides a low-voltage reactor double-layer insulating protective core resistant to high salt spray corrosion and its preparation method.

[0006] The technical solution provided in this application for a low-voltage reactor double-insulated protective core resistant to high salt spray corrosion and its preparation method is as follows: In the first aspect, a low-voltage reactor double-insulated protective iron core resistant to high salt spray corrosion includes a silicon steel sheet laminated iron core, an inner anti-rust insulating coating attached to the surface of the iron core, a coil wound on the outside of the iron core, and an outer corrosion-resistant insulating coating coated on the surface of the iron core and the coil. The inner anti-rust and insulating coating is formed by curing an inner insulating varnish, which comprises the following raw materials in parts by weight: The mixture consists of 45-50 parts of silicone-modified bisphenol F type epoxy resin, 14-18 parts of methyl phenyl silicone resin, 7-10 parts of nano zinc phosphate, 4-7 parts of mica powder, 2-5 parts of nano silica, 11-15 parts of polyamide curing agent, 1-3 parts of silane coupling agent KH-560, 0.5-1 part of defoamer, 0.5-1 part of leveling agent, and 0.5-2 parts of mixed solvent. The outer corrosion-resistant insulating coating is formed by curing an outer insulating varnish, which comprises the following raw materials in parts by weight: The mixture contains 50-53 parts of phenolic epoxy resin, 10-13 parts of fluorine-modified acrylic resin, 6-9 parts of strontium chromate, 8-10 parts of glass flakes, 3-5 parts of nano zinc oxide, 11-14 parts of alicyclic amine curing agent, 1-3 parts of salt spray resistant additive, 1-2 parts of ultraviolet absorber, and 1-3 parts of composite solvent.

[0007] The above technical solution employs a dual-layer functional protective structure consisting of an inner anti-rust insulating coating and an outer corrosion-resistant insulating coating, which respectively achieves the functions of rust prevention and passivation inside the iron core gaps and external corrosion medium barrier protection.

[0008] The inner insulating varnish adopts a composite film-forming system, which combines the high adhesion and high insulation of epoxy resin with the weather resistance and low surface energy of silicone resin. Combined with the chemical passivation effect of nano zinc phosphate, the physical barrier effect of mica powder, and the reinforcing effect of nano silica, it can fully penetrate and fill the gaps between silicon steel sheets, inhibiting internal corrosion from the source and reducing magnetic loss of equipment.

[0009] The outer insulating varnish uses a compound system of phenolic epoxy resin and fluorinated acrylic resin, which combines the labyrinth barrier effect of glass flakes, the electrochemical anti-rust effect of strontium chromate and the synergistic protective effect of nano zinc oxide to construct a dense physical barrier and chemical protective layer; the fluorinated acrylic resin further reduces the surface energy of the coating and significantly improves the barrier ability against chloride ions and acidic corrosive gases.

[0010] This effectively blocks corrosion channels through internal rust prevention and external corrosion isolation, completely solving the problems of core rusting and insulation breakdown in coastal and chemical areas; at the same time, the protective performance and salt spray resistance are greatly improved, and the coating remains stable without damage or peeling under temperature change conditions.

[0011] Preferably, the organosilicon-modified bisphenol F epoxy resin comprises the following raw materials in parts by weight: 66-70 parts of hydrogenated bisphenol F epoxy resin; 10-16 parts of carboxylated bisphenol F epoxy resin; 17-21 parts of epoxy-terminated polydimethylsiloxane; 0.2-0.5 parts of triphenylphosphine catalyst; Hydroquinone polymerization inhibitor 0.03-0.06 parts.

[0012] By adopting the above technical solution, hydrogenated bisphenol F and carboxylated bisphenol F are selected as epoxy resins, and epoxy-terminated polydimethylsiloxane is used as organosilicon monomers, which solves the problems of poor water resistance, insufficient flexibility and weak weather resistance.

[0013] Hydrogenated bisphenol F epoxy resin, free of benzene ring unsaturated bonds, significantly improves the coating's water resistance and chemical corrosion resistance, blocking the penetration channels of corrosive media. Carboxylated bisphenol F epoxy resin introduces active carboxyl groups, enhancing the resin's adhesion to silicon steel sheet substrates and its reactivity with the curing agent. Simultaneously, the carboxyl groups can chelate and disperse nano-zinc phosphate, improving the passivation and rust prevention effect on the iron core. Epoxy-terminated polydimethylsiloxane introduces organosilicon segments through chemical grafting, avoiding phase separation problems caused by physical blending. This increases the coating's density, effectively improving its flexibility, crack resistance, and low surface energy characteristics, and enhancing its stability under high and low temperature cycling conditions.

[0014] Preferably, the carboxylated bisphenol F epoxy resin is obtained by reacting maleic anhydride and bisphenol F epoxy resin, with a maleic anhydride substitution rate of 10-15%. The specific steps are as follows: 100 parts by weight of bisphenol F epoxy resin were dissolved in toluene and added to a reaction vessel. 3.5-5.3 parts by weight of maleic anhydride and 1.5-2.2 parts by weight of tetrabutylammonium bromide were dissolved in a mixed solvent of acetone and toluene with a volume ratio of 1:9 and added to the reaction vessel. The mixture was stirred and heated to 75-80℃ and reacted for 6-7 hours. The product was precipitated and washed with petroleum ether and dried under vacuum at 40-45℃ to obtain carboxylated bisphenol F epoxy resin.

[0015] By adopting the above technical solution, carboxyl groups are introduced by the ring-opening reaction of maleic anhydride and bisphenol F epoxy resin, while controlling the substitution rate to achieve a balance between the coating's water resistance and reactivity.

[0016] Preferably, the epoxy value of the hydrogenated bisphenol F epoxy resin is 0.52-0.55 eq / 100g, and the epoxy value of the epoxy-terminated polydimethylsiloxane is 0.18-0.22 eq / 100g.

[0017] By adopting the above technical solution, the crosslinking density of the cured coating is ensured to be moderate, while also having a certain degree of flexibility, ensuring the uniform distribution of organosilicon segments and reducing phase separation.

[0018] Preferably, the organosilicon-modified bisphenol F epoxy resin is prepared by the following steps: Add hydrogenated bisphenol F epoxy resin and carboxylated bisphenol F epoxy resin into the reactor, turn on nitrogen protection, heat to 80-100℃ and stir for 20-30 minutes to mix into a homogeneous transparent liquid. The triphenylphosphine catalyst and hydroquinone polymerization inhibitor were dissolved in epoxy-terminated polydimethylsiloxane and stirred until homogeneous to obtain a mixture. The mixture was then added dropwise to the reaction vessel over a period of 60-70 minutes. After the addition is complete, the temperature is raised to 112-115℃ and the reaction is carried out for 2.5-3 hours. The acid value is measured every 30 minutes. When the residual acid value of the system drops below 5mg KOH / g, the reaction is stopped, the temperature is lowered to below 60℃, and the silicone-modified bisphenol F type epoxy resin is discharged.

[0019] Preferably, the mixed solvent is prepared by mixing xylene and propylene glycol methyl ether at a mass ratio of 1:1.5-1.7; the composite solvent is selected as a low-aromatic, environmentally friendly composite solvent.

[0020] Using the above technical solution, the mixed solvent has a strong dissolving ability for the composite resin system and can adjust the viscosity to ensure that the paint can fully penetrate into the tiny gaps of the silicon steel sheet during vacuum impregnation. The composite solvent is environmentally friendly and can avoid defects such as sagging, pinholes, and orange peel during the spraying process, thereby improving the density and appearance quality of the coating.

[0021] Preferably, the thickness of the outer corrosion-resistant insulating coating is 70-80 μm.

[0022] By adopting the above technical solution, a balance between anti-salt spray performance and coating stability can be achieved by controlling the coating thickness.

[0023] Secondly, the method for preparing a double-insulated protective core for a low-voltage reactor resistant to high salt spray corrosion includes the following steps: S1 core pretreatment: Cut and stack silicon steel sheets into shape, remove iron filings and dust from the surface, clean with alkaline degreasing and pure water, and then dry for use; S2 Inner Layer Vacuum Impregnation and Curing: The inner layer insulating varnish is put into a vacuum impregnation tank, the vacuum degree is controlled at -0.085--0.1MPa, impregnated for 12-15 minutes, after depressurization, excess varnish is drained, pre-baked at 80-83℃ for 80-90 minutes, and then cured at 135-140℃ for 140-150 minutes, and then naturally cooled to room temperature; S3 coil winding and assembly: The coil is wound on the outside of the iron core after the inner layer protection is completed, the overall structure is tightened, and the lead wire part is insulated and wrapped. S4 outer layer electrostatic spraying curing: The outer layer of insulating paint is sprayed in two coats using electrostatic spraying process. The dry film thickness of each coat is 35-40μm. After spraying, it is placed in an environment of 155-160℃ for constant temperature curing for 180-200min. S5 Finished Product Inspection and Sealing: Complete insulation withstand voltage and salt spray sampling performance tests, and perform sealing protection treatment on the wiring terminals to obtain the finished protective iron core.

[0024] The above technical solution employs a combination of vacuum impregnation and stepped curing, along with a double-layer high-voltage electrostatic spraying process. Vacuum impregnation ensures that the inner insulating varnish is completely filled, achieving comprehensive rust prevention. Stepped curing gradually releases the solvent, eliminating internal stress in the coating and preventing cracking and blistering. Two spraying processes ensure coating uniformity and avoid sagging defects caused by excessive thickness in a single spraying.

[0025] Preferably, the voltage for electrostatic spraying is set to 60-80kV.

[0026] By adopting the above technical solution, the voltage range can ensure that the paint mist has good diffraction on complex parts such as the corners and joints of the iron core, avoiding missed coating or thin coating.

[0027] Preferably, the viscosity of the inner insulating varnish in the fourth cup is controlled to be 28-32 s, and the viscosity of the outer insulating varnish in the fourth cup is controlled to be 22-26 s.

[0028] In summary, this application has at least one of the following beneficial effects: 1. It adopts a dual-layer functional protection structure with an inner anti-rust insulating coating and an outer corrosion-resistant insulating coating, which respectively achieves the functions of rust prevention and passivation inside the iron core gaps and external corrosion medium barrier protection.

[0029] The inner insulating varnish adopts a composite film-forming system, which combines the high adhesion and high insulation of epoxy resin with the weather resistance and low surface energy of silicone resin. Combined with the chemical passivation effect of nano zinc phosphate, the physical barrier effect of mica powder, and the reinforcing effect of nano silica, it can fully penetrate and fill the gaps between silicon steel sheets, inhibiting internal corrosion from the source and reducing magnetic loss of equipment.

[0030] The outer insulating varnish uses a compound system of phenolic epoxy resin and fluorinated acrylic resin, which combines the labyrinth barrier effect of glass flakes, the electrochemical anti-rust effect of strontium chromate and the synergistic protective effect of nano zinc oxide to construct a dense physical barrier and chemical protective layer; the fluorinated acrylic resin further reduces the surface energy of the coating and significantly improves the barrier ability against chloride ions and acidic corrosive gases.

[0031] This effectively blocks corrosion channels through internal rust prevention and external corrosion isolation, completely solving the problems of core rusting and insulation breakdown in coastal and chemical areas; at the same time, the protective performance and salt spray resistance are greatly improved, and the coating remains stable without damage or peeling under temperature change conditions.

[0032] 2. Hydrogenated bisphenol F and carboxylated bisphenol F were selected as epoxy resins, and epoxy-terminated polydimethylsiloxane was selected as organosilicon monomers to solve the problems of poor water resistance, insufficient flexibility and weak weather resistance.

[0033] Hydrogenated bisphenol F epoxy resin, free of benzene ring unsaturated bonds, significantly improves the coating's water resistance and chemical corrosion resistance, blocking the penetration channels of corrosive media. Carboxylated bisphenol F epoxy resin introduces active carboxyl groups, enhancing the resin's adhesion to silicon steel sheet substrates and its reactivity with the curing agent. Simultaneously, the carboxyl groups can chelate and disperse nano-zinc phosphate, improving the passivation and rust prevention effect on the iron core. Epoxy-terminated polydimethylsiloxane introduces organosilicon segments through chemical grafting, avoiding phase separation problems caused by physical blending. This increases the coating's density, effectively improving its flexibility, crack resistance, and low surface energy characteristics, and enhancing its stability under high and low temperature cycling conditions. Detailed Implementation

[0034] The present application will be further described in detail below with reference to Examples 1-3 and Comparative Examples 1-2.

[0035] Preparation Example

[0036] Preparation Example 1 Organosilicon-modified bisphenol F type epoxy resin includes the following raw materials: Hydrogenated bisphenol F epoxy resin 66kg, epoxy value 0.53-0.56eq / 100g, brand name Mitsubishi Chemical (Japan) YL-6753; 10 kg of carboxylated bisphenol F epoxy resin was obtained by reacting maleic anhydride with bisphenol F epoxy resin. The maleic anhydride substitution rate was 10%, and the epoxy value of the bisphenol F epoxy resin was 0.51-0.54 eq / 100g. The brand name was BASF Epikote 862. 17 kg of epoxy-terminated dimethylsiloxane, with an epoxy value of 0.19-0.21 eq / 100g, brand name: Silicon Friends Cloud End-Terminated Epoxy Silicone Oil (10000).

[0037] 0.2 kg of triphenylphosphine catalyst; Hydroquinone polymerization inhibitor 0.03 kg; Organosilicon-modified bisphenol F epoxy resin is prepared by the following method: 100 kg of bisphenol F epoxy resin was dissolved in toluene and added to a reaction vessel. 3.5 kg of maleic anhydride and 1.5 kg of tetrabutylammonium bromide were dissolved in a mixed solvent of acetone and toluene with a volume ratio of 1:9 and added to the reaction vessel. The mixture was stirred and heated to 75 °C and reacted for 6 h. The product was precipitated with petroleum ether, washed, and dried under vacuum at 40 °C to obtain carboxylated bisphenol F epoxy resin. Hydrogenated bisphenol F epoxy resin and carboxylated bisphenol F epoxy resin were added to the reactor, nitrogen protection was turned on, the temperature was raised to 80°C and stirred for 30 minutes to form a homogeneous transparent liquid. Triphenylphosphine catalyst and hydroquinone polymerization inhibitor were dissolved in epoxy-terminated polydimethylsiloxane and stirred until homogeneous to obtain a mixture. The mixture was then added dropwise to the reaction vessel over a period of 60 minutes. After the addition is complete, the temperature is raised to 112℃ and reacted for 2.5 hours. The acid value is measured every 30 minutes. When the residual acid value of the system drops below 5 mg KOH / g, the reaction is stopped, the temperature is lowered to below 60℃, and the silicone-modified bisphenol F type epoxy resin is discharged.

[0038] Preparation Example 2 Organosilicon-modified bisphenol F type epoxy resin includes the following raw materials: 70kg of hydrogenated bisphenol F epoxy resin, epoxy value 0.54-0.58eq / 100g, brand name Yixing Yincheng Chemical ST-3000; 16 kg of carboxylated bisphenol F epoxy resin was obtained by reacting maleic anhydride and bisphenol F epoxy resin. The maleic anhydride substitution rate was 15%, and the epoxy value of the bisphenol F epoxy resin was 0.51-0.54 eq / 100g. The brand name was Nan Ya NPEL-170. Epoxy-terminated dimethylsiloxane 21kg, epoxy value 0.18-0.22eq / 100g, brand name Shanghai Shenrong SR-EX10.

[0039] 0.5 kg of triphenylphosphine catalyst; Hydroquinone polymerization inhibitor 0.06 kg; Organosilicon-modified bisphenol F epoxy resin is prepared by the following method: 100 kg of bisphenol F epoxy resin was dissolved in toluene and added to a reaction vessel. 5.3 kg of maleic anhydride and 2.2 kg of tetrabutylammonium bromide were dissolved in a mixed solvent of acetone and toluene with a volume ratio of 1:9 and added to the reaction vessel. The mixture was stirred and heated to 80 °C and reacted for 7 h. The product was precipitated with petroleum ether, washed, and dried under vacuum at 45 °C to obtain carboxylated bisphenol F epoxy resin. Hydrogenated bisphenol F epoxy resin and carboxylated bisphenol F epoxy resin were added to the reactor, nitrogen protection was turned on, the temperature was raised to 100℃ and stirred for 20 minutes to form a homogeneous transparent liquid. Triphenylphosphine catalyst and hydroquinone polymerization inhibitor were dissolved in epoxy-terminated polydimethylsiloxane and stirred until homogeneous to obtain a mixture. The mixture was then added dropwise to the reaction vessel over a period of 70 minutes. After the addition is complete, the temperature is raised to 115℃ and reacted for 3 hours. The acid value is measured every 30 minutes. When the residual acid value of the system drops below 5 mg KOH / g, the reaction is stopped, the temperature is lowered to below 60℃, and the silicone-modified bisphenol F type epoxy resin is discharged. Example

[0040] Example 1 This embodiment discloses a double-insulated protective iron core for a low-voltage reactor resistant to high salt spray corrosion, including a silicon steel sheet laminated iron core, an inner anti-rust insulating coating attached to the surface of the iron core, a coil wound on the outside of the iron core, and an outer corrosion-resistant insulating coating coated on the surface of the iron core and the coil. The inner rust-proof and insulating coating is formed by curing an inner insulating varnish, which includes the following raw materials: 45 kg of organosilicon-modified bisphenol F type epoxy resin was prepared from the following ingredients: 14 kg of methyl phenyl organosilicon resin, 7 kg of nano zinc phosphate, 4 kg of mica powder, 2 kg of nano silica, 11 kg of polyamide curing agent, 1 kg of silane coupling agent KH-560, 0.5 kg of defoamer, 0.5 kg of leveling agent, and 0.5 kg of mixed solvent. The solvent was prepared by mixing xylene and propylene glycol methyl ether at a mass ratio of 1:1.5. The outer corrosion-resistant insulating coating is formed by curing an outer insulating varnish. The thickness of the outer corrosion-resistant insulating coating is 70μm. The outer insulating varnish includes the following raw materials: The mixture consists of 50 kg of phenolic epoxy resin, 10 kg of fluorine-modified acrylic resin, 6 kg of strontium chromate, 8 kg of glass flakes, 3 kg of nano zinc oxide, 11 kg of alicyclic amine curing agent, 1 kg of salt spray resistant additive, 1 kg of ultraviolet absorber, and 1 kg of composite solvent. Low-aromatic, environmentally friendly composite solvent is selected.

[0041] The preparation method of the above-mentioned low-voltage reactor double-insulated protective core resistant to high salt spray corrosion includes the following steps: S1 core pretreatment: Silicon steel sheets are cut and stacked into shape, iron filings and dust are removed from the surface, and the core is cleaned by alkaline degreasing and washing with pure water and then dried for use.

[0042] S2 Inner Layer Vacuum Impregnation and Curing: Weigh out silicone-modified bisphenol F type epoxy resin and methyl phenyl silicone resin, add them to a mixed solvent and stir until completely dissolved. Add zinc phosphate rust inhibitor, flake mica powder, and nano silica to the mixture. After high-speed dispersion, grind the mixture until the fineness is qualified. Then add polyamide curing agent, silane coupling agent KH-560, defoamer, and leveling agent. Stir thoroughly and evenly. After filtration, the finished inner layer insulating varnish is obtained. The viscosity of the 4-cup of the Coater is measured to be 30s. The inner insulating varnish is placed in a vacuum impregnation tank with a vacuum degree controlled at -0.085MPa and an impregnation time of 12 minutes. After depressurization, excess varnish is drained. The inner rust-proof insulating coating is obtained by pre-baking at 80℃ for 90 minutes, curing at 135℃ for 150 minutes, and then naturally cooling to room temperature.

[0043] S3 coil winding and assembly: The coil is wound on the outside of the iron core after the inner layer protection is completed, the overall structure is tightened, and the lead wire part is insulated and wrapped.

[0044] S4 outer layer electrostatic spraying curing: Phenolic epoxy resin and fluorine-modified acrylic resin are added to an environmentally friendly composite solvent and stirred and dispersed. Strontium chromate anti-rust pigment, ultrafine glass flakes and nano zinc oxide are added to it. After grinding and homogenization, alicyclic amine curing agent, salt spray resistant additive and ultraviolet absorber are added. After stirring and filtering, the outer layer insulating paint is obtained. The actual measured viscosity of the 4-cup coating is 24s. The outer insulating varnish was applied in two coats using an electrostatic spraying process. The electrostatic spraying voltage was set to 60kV, and the dry film thickness of a single coat was 35μm. After spraying, the coating was placed in a constant temperature environment of 155℃ for 200min to obtain the outer corrosion-resistant insulating coating.

[0045] S5 Finished Product Inspection and Sealing: Complete insulation withstand voltage and salt spray sampling performance tests, and perform sealing protection treatment on the wiring terminals to obtain the finished protective iron core.

[0046] Example 2 This embodiment discloses a double-insulated protective iron core for a low-voltage reactor resistant to high salt spray corrosion, including a silicon steel sheet laminated iron core, an inner anti-rust insulating coating attached to the surface of the iron core, a coil wound on the outside of the iron core, and an outer corrosion-resistant insulating coating coated on the surface of the iron core and the coil. The inner rust-proof and insulating coating is formed by curing an inner insulating varnish, which includes the following raw materials: 50 kg of organosilicon-modified bisphenol F type epoxy resin was prepared from the following ingredients: 18 kg of methyl phenyl organosilicon resin, 10 kg of nano zinc phosphate, 7 kg of mica powder, 5 kg of nano silica, 15 kg of polyamide curing agent, 3 kg of silane coupling agent KH-560, 1 kg of defoamer, 1 kg of leveling agent, and 2 kg of mixed solvent. The solvent was prepared by mixing xylene and propylene glycol methyl ether at a mass ratio of 1:1.7. The outer corrosion-resistant insulating coating is formed by curing an outer insulating varnish. The thickness of the outer corrosion-resistant insulating coating is 70μm. The outer insulating varnish includes the following raw materials: The mixture consists of 53 kg of phenolic epoxy resin, 13 kg of fluorine-modified acrylic resin, 9 kg of strontium chromate, 10 kg of glass flakes, 5 kg of nano zinc oxide, 14 kg of alicyclic amine curing agent, 3 kg of salt spray resistant additive, 2 kg of ultraviolet absorber, and 3 kg of composite solvent. Low-aromatic, environmentally friendly composite solvent is selected.

[0047] The preparation method of the above-mentioned low-voltage reactor double-insulated protective core resistant to high salt spray corrosion includes the following steps: S1 core pretreatment: Silicon steel sheets are cut and stacked into shape, iron filings and dust are removed from the surface, and the core is cleaned by alkaline degreasing and washing with pure water and then dried for use.

[0048] S2 Inner Layer Vacuum Impregnation and Curing: Weigh out silicone-modified bisphenol F type epoxy resin and methyl phenyl silicone resin, add them to a mixed solvent and stir until completely dissolved. Add zinc phosphate rust inhibitor, flake mica powder, and nano silica to the mixture. After high-speed dispersion, grind the mixture until the fineness is qualified. Then add polyamide curing agent, silane coupling agent KH-560, defoamer, and leveling agent. Stir thoroughly and evenly. After filtration, the finished inner layer insulating varnish is obtained. The viscosity of the 4-cup coating is measured to be 32s. The inner insulating varnish is placed in a vacuum impregnation tank with a vacuum degree controlled at -0.1MPa and an impregnation time of 15 minutes. After depressurization, excess varnish is drained. The inner rust-proof insulating coating is obtained by pre-baking at 83℃ for 80 minutes, curing at 140℃ for 140 minutes, and then naturally cooling to room temperature.

[0049] S3 coil winding and assembly: The coil is wound on the outside of the iron core after the inner layer protection is completed, the overall structure is tightened, and the lead wire part is insulated and wrapped.

[0050] S4 outer layer electrostatic spraying curing: Phenolic epoxy resin and fluorine-modified acrylic resin are added to an environmentally friendly composite solvent and stirred and dispersed. Strontium chromate anti-rust pigment, ultrafine glass flakes and nano zinc oxide are added to it. After grinding and homogenization, alicyclic amine curing agent, salt spray resistant additive and ultraviolet absorber are added. After stirring and filtering, the outer layer insulating paint is obtained. The actual measured viscosity of Coating Cup 4 is 22s. The outer layer of insulating varnish was applied in two coats using an electrostatic spraying process. The electrostatic spraying voltage was set to 80kV, and the dry film thickness of a single coat was 40μm. After spraying, the coating was placed in a constant temperature environment of 160℃ for 180min to obtain the outer corrosion-resistant insulating coating.

[0051] S5 Finished Product Inspection and Sealing: Complete insulation withstand voltage and salt spray sampling performance tests, and perform sealing protection treatment on the wiring terminals to obtain the finished protective iron core.

[0052] Example 3 The difference between this embodiment and Embodiment 1 is that the inner insulating varnish used in the inner anti-rust insulating coating of the protective iron core and the outer insulating varnish used in the outer corrosion resistant insulating coating are different.

[0053] In this embodiment, the inner insulating varnish comprises the following raw materials in parts by weight: 48 kg of organosilicon-modified bisphenol F type epoxy resin was prepared from the following ingredients: 17 kg of methyl phenyl organosilicon resin, 9 kg of nano zinc phosphate, 5 kg of mica powder, 3 kg of nano silica, 13 kg of polyamide curing agent, 2 kg of silane coupling agent KH-560, 0.8 kg of defoamer, 0.7 kg of leveling agent, and 1.5 kg of mixed solvent. The outer insulating varnish comprises the following raw materials in parts by weight: 50-53 parts phenolic epoxy resin, 10-13 parts fluorine-modified acrylic resin, 6-9 parts strontium chromate, 8-10 parts glass flakes, 3-5 parts nano zinc oxide, 11-14 parts alicyclic amine curing agent, 1-3 parts salt spray resistant additive, 1-2 parts ultraviolet absorber, and 1-3 parts composite solvent. Comparative Example

[0054] Comparative Example 1 The difference between this comparative example and Example 1 is that the inner insulating varnish used in the inner rust-proof insulating coating of the protective iron core is different.

[0055] In this comparative example, the silicone-modified bisphenol F type epoxy resin in the inner insulating varnish was not the resin obtained in Preparation Example 1, but a commercially available silicone-modified epoxy resin purchased from Shenzhen Anpin Silicone Co., Ltd.

[0056] Comparative Example 2 The difference between this comparative example and Example 1 is that the inner insulating varnish used in the inner anti-rust insulating coating of the protective iron core and the outer insulating varnish used in the outer corrosion resistant insulating coating are different.

[0057] In this comparative example, both the inner and outer insulating varnishes were made from commercially available epoxy insulating varnishes. The specific formula was as follows: 50 kg of bisphenol F epoxy resin, 20 kg of polymethylphenylsiloxane silicone resin, 12 kg of pigments and fillers, 18 kg of curing agent, 0.3 kg of defoamer, 0.5 kg of leveling agent, 0.3 kg of thickener, and 20 kg of deionized water.

[0058] Performance testing

[0059] The following performance tests were conducted on the double-insulated protective iron cores prepared in Examples 1-3 and Comparative Examples 1-2: Example 1 ≥2000h Level 0 24 No rust for 8 years Example 2 ≥2000h Level 0 22 No rust for 8 years Example 3 ≥2000h Level 0 25 No rust for 8 years Comparative Example 1 ≤1500h Level 1 20 Rust spots will appear in 5-6 years. Comparative Example 2 ≤500h Level 2 17 Rust spots will appear in 1-2 years. As shown in the table above, the insulating protective core of this application adopts a double-layer independent formula functional protective structure, combined with vacuum impregnation, stepped curing, and double-layer electrostatic spraying processes. The components of the inner and outer insulating varnishes are independent of each other, respectively achieving the functions of rust prevention and passivation inside the core gaps and barrier protection against external corrosive media. Compared with the traditional single-coating protection mode, the protective performance is greatly improved. The product's resistance to neutral salt spray exceeds 2000 hours, the electrical breakdown strength meets the standard, and the coating remains stable without damage or peeling under temperature change conditions, effectively extending the service life of reactors under harsh operating conditions.

[0060] For silicone-modified bisphenol F type epoxy resin, this application introduces active carboxyl groups by replacing the unsaturated bonds of the benzene ring with hydrogenation, which further improves the water resistance and flexibility of the epoxy resin, while also enhancing the passivation and rust prevention effect of the inner insulating coating on the iron core.

[0061] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this specific embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A double-insulated protective iron core for a low-voltage reactor resistant to high salt spray corrosion, characterized in that: It includes a silicon steel sheet laminated iron core, an inner anti-rust insulating coating attached to the surface of the iron core, a coil wound on the outside of the iron core, and an outer corrosion-resistant insulating coating coated on the surface of the iron core and the coil. The inner anti-rust and insulating coating is formed by curing an inner insulating varnish, which comprises the following raw materials in parts by weight: The mixture consists of 45-50 parts of silicone-modified bisphenol F type epoxy resin, 14-18 parts of methyl phenyl silicone resin, 7-10 parts of nano zinc phosphate, 4-7 parts of mica powder, 2-5 parts of nano silica, 11-15 parts of polyamide curing agent, 1-3 parts of silane coupling agent KH-560, 0.5-1 part of defoamer, 0.5-1 part of leveling agent, and 0.5-2 parts of mixed solvent. The organosilicon-modified bisphenol F epoxy resin comprises the following raw materials in parts by weight: 66-70 parts of hydrogenated bisphenol F epoxy resin, 10-16 parts of carboxylated bisphenol F epoxy resin, 17-21 parts of epoxy-terminated polydimethylsiloxane, 0.2-0.5 parts of triphenylphosphine catalyst, and 0.03-0.06 parts of hydroquinone polymerization inhibitor; The outer corrosion-resistant insulating coating is formed by curing an outer insulating varnish, which comprises the following raw materials in parts by weight: The mixture contains 50-53 parts of phenolic epoxy resin, 10-13 parts of fluorine-modified acrylic resin, 6-9 parts of strontium chromate, 8-10 parts of glass flakes, 3-5 parts of nano zinc oxide, 11-14 parts of alicyclic amine curing agent, 1-3 parts of salt spray resistant additive, 1-2 parts of ultraviolet absorber, and 1-3 parts of composite solvent.

2. The double-insulated protective core of a low-voltage reactor resistant to high salt spray corrosion according to claim 1, characterized in that: The carboxylated bisphenol F epoxy resin is obtained by reacting maleic anhydride and bisphenol F epoxy resin, with a maleic anhydride substitution rate of 10-15%. The specific steps are as follows: 100 parts by weight of bisphenol F epoxy resin were dissolved in toluene and added to a reaction vessel. 3.5-5.3 parts by weight of maleic anhydride and 1.5-2.2 parts by weight of tetrabutylammonium bromide were dissolved in a mixed solvent of acetone and toluene with a volume ratio of 1:9 and added to the reaction vessel. The mixture was stirred and heated to 75-80℃ and reacted for 6-7 hours. The product was precipitated and washed with petroleum ether and dried under vacuum at 40-45℃ to obtain carboxylated bisphenol F epoxy resin.

3. The double-insulated protective core of a low-voltage reactor resistant to high salt spray corrosion according to claim 2, characterized in that: The hydrogenated bisphenol F epoxy resin has an epoxy value of 0.52-0.55 eq / 100g, and the epoxy-terminated polydimethylsiloxane has an epoxy value of 0.18-0.22 eq / 100g.

4. The double-insulated protective core of a low-voltage reactor resistant to high salt spray corrosion according to claim 1, characterized in that: The organosilicon-modified bisphenol F epoxy resin is prepared through the following steps: Add hydrogenated bisphenol F epoxy resin and carboxylated bisphenol F epoxy resin into the reactor, turn on nitrogen protection, heat to 80-100℃ and stir for 20-30 minutes to mix into a homogeneous transparent liquid. Triphenylphosphine catalyst and hydroquinone polymerization inhibitor were dissolved in epoxy-terminated polydimethylsiloxane and stirred until homogeneous to obtain a mixture. The mixture was then added dropwise to the reaction vessel over a period of 60-70 minutes. After the addition is complete, the temperature is raised to 112-115℃ and the reaction is carried out for 2.5-3 hours. The acid value is measured every 30 minutes. When the residual acid value of the system drops below 5mg KOH / g, the reaction is stopped, the temperature is lowered to below 60℃, and the silicone-modified bisphenol F type epoxy resin is discharged.

5. The double-insulated protective core of a low-voltage reactor resistant to high salt spray corrosion according to claim 1, characterized in that: The mixed solvent is prepared by mixing xylene and propylene glycol methyl ether at a mass ratio of 1:1.5-1.

7.

6. The double-insulated protective core of a low-voltage reactor resistant to high salt spray corrosion according to claim 1, characterized in that: The thickness of the outer corrosion-resistant insulating coating is 70-80 μm.

7. The method for preparing the double-layer insulated protective core of a low-voltage reactor resistant to high salt spray corrosion as described in any one of claims 1-6, characterized in that, Includes the following steps: S1 core pretreatment: Cut and stack silicon steel sheets into shape, remove iron filings and dust from the surface, clean with alkaline degreasing and pure water, and then dry for use; S2 Inner Layer Vacuum Impregnation and Curing: The inner layer insulating varnish is put into a vacuum impregnation tank, the vacuum degree is controlled at -0.085--0.1MPa, impregnated for 12-15 minutes, after depressurization, excess varnish is drained, pre-baked at 80-83℃ for 80-90 minutes, and then cured at 135-140℃ for 140-150 minutes, and then naturally cooled to room temperature; S3 coil winding and assembly: The coil is wound on the outside of the iron core after the inner layer protection is completed, the overall structure is tightened, and the lead wire part is insulated and wrapped. S4 outer layer electrostatic spraying curing: The outer layer of insulating paint is sprayed in two coats using electrostatic spraying process. The dry film thickness of each coat is 35-40μm. After spraying, it is placed in an environment of 155-160℃ for constant temperature curing for 180-200min. S5 Finished Product Inspection and Sealing: Complete insulation withstand voltage and salt spray sampling performance tests, and perform sealing protection treatment on the wiring terminals to obtain the finished protective iron core.

8. The method for preparing the double-layer insulated protective core of a low-voltage reactor resistant to high salt spray corrosion according to claim 7, characterized in that: The voltage for electrostatic spraying is set to 60-80kV.

9. The method for preparing the double-layer insulated protective core of a low-voltage reactor resistant to high salt spray corrosion according to claim 7, characterized in that: The viscosity of the inner insulating varnish at the fourth cup is controlled to be 28-32 s, and the viscosity of the outer insulating varnish at the fourth cup is controlled to be 22-26 s.

Citation Information

Patent Citations

  • Environment-friendly high-solid-content anticorrosive paint and preparation method thereof

    CN120795754A

  • High-temperature-resistant wear-resistant anticorrosive paint for oil field and preparation method thereof

    CN122188434A

  • Novel deformer

    CN205862948U